Islamic Preaching Content on Instagram and Generation Z Interest in Islamic Studies - Ristanti, Mery; Wardani, Dian Kusuma; Qosim, Nanang (Al-MUNZIR, 2026)
This study investigates the presence of Islamic preaching (da’wah) content on Instagram and its influence on Generation Z’s interest in Islamic studies. The rapid growth of digital technology has transformed Instagram into an effective platform for delivering religious messages in a creative, interactive, and easily accessible manner, particularly for young audiences. This research adopts a quantitative approach using a descriptive associative design. Data were collected through questionnaires distributed to Generation Z individuals living in Dukuh Hamlet, Sidokaton Village, Kudu District, Jombang Regency, who actively use Instagram as a source of information and entertainment. The study employed a quota sampling technique, whereby respondents possessing predetermined characteristics were selected until the required sample quota was fulfilled. The relationship between da’wah content and interest in Islamic studies was analyzed using simple linear regression. The results indicate that da’wah content on Instagram has a positive and significant influence on Generation Z’s interest in Islamic studies, as evidenced by a calculated t-value of 3.798, which exceeds the t-table value of 1.701. Factors contributing to this increased interest include the clarity of religious messages, creative content presentation, relevance to everyday life, the use of contemporary communication styles, and consistency in content delivery. These findings underscore the importance of effective digital da’wah strategies in enhancing engagement and encouraging sustained participation of Generation Z in Islamic learning activities.